IOS forensics for investigators : take mobile forensics to the next level by analyzing, extracting, and reporting sensitive evidence /: take mobile forensics to the next level by analyzing, extracting, and reporting sensitive evidence. (2022) - Tiepolo, Gianluca
No abstract available